Advancing schistosomiasis surveillance: standardization and application of an environmental DNA (eDNA)-based approach for detecting Schistosoma mansoni in Brazil - Sandra Grossi Gava; Isadora Rodrigues de Carvalho; Marcello Otake Sato; Megumi Sato; Natália de Melo Nasser Fava; Patrícia Martins Parreiras; Aureo Almeida de Oliveira; Sueleny Silva Ferreira Teixeira; Adelina Junia Lourenço; Omar dos Santos Carvalho; Lângia Colli Montresor; Marina Moraes Mourão; et al. (BMC Infectious Diseases)
Abstract Background Schistosoma sp. transmission is linked to water bodies, poor sanitation, and the presence of intermediate hosts. Nevertheless, parasite detection in snails is hampered by challenges in snail sampling and low infection rates, mainly in moderate and low-endemic areas, as well as requiring specialized personnel and being time-consuming. Thus, there is a need to improve tools to assist schistosomiasis surveillance and an environmental DNA (eDNA) approach may help to overcome these limitations. Here, we standardized and used an eDNA-based approach to monitor Schistosoma mansoni occurrence in two schistosomiasis endemic areas from Minas Gerais, Brazil. Methods The eDNA approach was standardized for local conditions by evaluating the specificity of the qPCR assay in detecting the parasite DNA. Water from snail breeding tanks containing Biomphalaria glabrata, either infected or not with S. mansoni, was used to standardize the eDNA filtration and extraction protocols. Three molecular techniques– Low-Stringency PCR (LS-PCR), Loop-mediated isothermal amplification (LAMP), and quantitative PCR (qPCR)– were applied to investigate samples from snail tanks and two field surveys. Additionally, malacological surveys and measurements of water physicochemical and microbiological parameters were conducted at the same locations to know the species of mollusks present and the ideal environmental conditions to identify hotspots. Results The qPCR assay was specifically amplified Schistosoma sp. DNA without amplifying other trematodes presents in Brazil, ensuring accurate detection without cross-amplification. All three molecular assays efficiently detected S. mansoni DNA only from eDNA samples from tanks with infected snails. The eDNA approach, associated with LAMP and qPCR assays, successfully identified S. mansoni DNA at the same collection points where snails releasing cercariae were found and at one additional site, that was missed by traditional methods, underscoring its sensitivity. Conclusions This study illustrates the potential of employing eDNA sampling combined with molecular techniques as an effective strategy for monitoring and identifying potential schistosomiasis transmission foci in endemic areas. This approach aligns with the WHO’s roadmap for schistosomiasis elimination by 2030 and has implications for public health interventions and control measures.